2018
DOI: 10.3390/md16060199
|View full text |Cite
|
Sign up to set email alerts
|

Albisporachelin, a New Hydroxamate Type Siderophore from the Deep Ocean Sediment-Derived Actinomycete Amycolatopsis albispora WP1T

Abstract: Marine actinobacteria continue to be a rich source for the discovery of structurally diverse secondary metabolites. Here we present a new hydroxymate siderophore produced by Amycolatopsis albispora, a recently described species of this less explored actinomycete genus. Strain WP1T was isolated from sediments collected at −2945 m in the Indian Ocean. The new siderophore, designated albisporachelin, was isolated from iron depleted culture broths and the structure was established by 1D and 2D NMR and MS/MS experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Siderophore production has been demonstrated by Streptomyces strains that produce hydroxamate-type siderophores known as deferoxamine [ 20 ]. Moreover, heterobactins are catecholate-hydroximate mixed-type siderophores that have been found in Rhodococcus erythropolis [ 46 ], and albisporachelin is a hydroxamate-type siderophore produced by Amycolatopsis albispora [ 47 ]. A sufficient amount of siderophore production by biocontrol agents limits Fe 3+ availability for phytopathogenic fungi.…”
Section: Main Actinomycete Antagonistic Mechanisms To Phytopathogenic...mentioning
confidence: 99%
“…Siderophore production has been demonstrated by Streptomyces strains that produce hydroxamate-type siderophores known as deferoxamine [ 20 ]. Moreover, heterobactins are catecholate-hydroximate mixed-type siderophores that have been found in Rhodococcus erythropolis [ 46 ], and albisporachelin is a hydroxamate-type siderophore produced by Amycolatopsis albispora [ 47 ]. A sufficient amount of siderophore production by biocontrol agents limits Fe 3+ availability for phytopathogenic fungi.…”
Section: Main Actinomycete Antagonistic Mechanisms To Phytopathogenic...mentioning
confidence: 99%
“…A novel albisporachelin siderophore ( 33 ) was obtained from iron-depleted culture broths of marine actinomycete Amycolatopsis albispora WP1 T . The study of iron-chelating ability suggested that its hydroxamate moieties were involved in iron binding, which was consistent with its structure [37]. Moreover, the variable siderophore metabolome of the marine actinomycete Salinispora tropica CNB-440 revealed the production of six known siderophores, desferrioxamine A 1 , A 2 , B, D 1 , D 2 , and E ( 34 – 39 ), and one novel siderophore desferrioxamine N ( 40 ) [38].…”
Section: Diversity Of Siderophores From Marine Microorganismsmentioning
confidence: 79%
“…Several of these BGCs appear to be unique and could not be identified in the publicly available genomes of other bacteria ( Table S4 , Supplemental Information ). The vast majority of BGCs identified in the genome of YIM10 had homologs in the genome of recently described Amycolatopsis albispora WP1 isolated from marine sediment ( Wu et al., 2018 ), suggesting that these strains are closely related.…”
Section: Resultsmentioning
confidence: 95%